2017
DOI: 10.1021/acs.jpcc.7b07296
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Bromination of N-Phenylacetamide Inside CNTs. Are CNTs Real Nanoreactors Controlling Regioselectivity and Kinetics? A QM/MM Investigation

Abstract: We carried out a computational investigation on the mechanism of the bromination reaction of N-phenylacetamide inside CNTs, in water, and in an aprotic solvent (ethylbenzene). A full QM and a QM/MM approach was used. In the aprotic solvent, a Wheland intermediate (ion pair formed by arenium ion and chloride) exists only for the attack in the ortho position, while the para attack proceeds in a concerted manner (concerted direct substitution). The reaction is catalyzed by the HCl byproduct, which lowers signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The experiment with SWCNTs of different dimensions confirmed that subtle variations in CNT diameter (i.e., from 6.9 to 9.6 Å) are crucial to get the desired effect. The in silico study of this reaction led to the hypothesis that the non-covalent interactions within CNTs is the main contributing factor to explain the regioselectivity and the kinetics of the reaction [37]. The following examples are dedicated to the second type-reactions where the process occurs inside CNTs and the product remains encapsulated.…”
Section: Nanoreactors-reactions Type I and Iimentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment with SWCNTs of different dimensions confirmed that subtle variations in CNT diameter (i.e., from 6.9 to 9.6 Å) are crucial to get the desired effect. The in silico study of this reaction led to the hypothesis that the non-covalent interactions within CNTs is the main contributing factor to explain the regioselectivity and the kinetics of the reaction [37]. The following examples are dedicated to the second type-reactions where the process occurs inside CNTs and the product remains encapsulated.…”
Section: Nanoreactors-reactions Type I and Iimentioning
confidence: 99%
“…Molecular model and TEM simulation of a bucky metallocene reorganizing to form a C 70 fullerene (B). Adapted with permission from reference[37]. Copyright (2011) American Chemical Society.…”
mentioning
confidence: 99%
“…Following this hypothesis, increasing attention has been focused during the last years on the use of carbon nanomaterials as catalysts . These materials are particularly interesting and promising for a sustainable chemistry in many industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…Computational chemistry could be helpful in this concern, but relatively few computational studies have been published on the operating mode of supramolecular catalysts, [8,9,[17][18][19][20] although things may have changed in the last two years. [21][22][23][24] The systems are intrinsically challenging for computational chemistry: a large number of conformers, complicated reaction networks, and need for a sufficiently accurate description of weak interactions.…”
Section: Introductionmentioning
confidence: 99%